Tratamento de esgoto sanitário gerado na infraestrutura de apoio da indústria de minério de ferro: estudo de caso em uma mina de médio porte no quadrilátero ferrífero - Fernanda Narciso Maximiano Barcellos (2019)
The majority of the mining areas are located in rural areas and therefore it is necessary to seek environmentally appropriate alternatives for the treatment and final disposal of sewage from the installed support areas on mining complexes. In this context, decentralized, compact and precast sewage treatment plants become a well-applied alternative on mining sites. The present study seeks to bring a practical contribution to the mining sector and to the Compact Sewage Treatment Plants (CSTP) manufacturers, promoting a critical analysis of five units installed in a medium - sized iron mining in the Quadrilátero Ferrífero. The main objectives of this study are: i) qualitative and quantitative characterization of the per capita contribution of sewage from different mining support facilities; ii) evaluation of the suitability of the engineering projects of the compact sewage treatment plants implanted on mining site; and iii) evaluation of the efficiencies and performance of the CSTP, as well as the levels of compliance with the standards recommended by the environmental legislation. For the study, five systems were selected, of three different sizes: i) small (1,6 m³/day); medium (7,7 m³/day); and large (60,0 m³/day). All of them consist of anaerobic reactors followed by submerged aerated biofilters. The adopted methodology considers the installation of devices to determine the inflows generated in the supporting infrastructures, the analysis of the projects and the technical specifications of the systems selected for this study, the statistical evaluation and analysis of the historical series of monitoring data (BOD, COD and TSS). From data analysis and interpretation, the measured flow values were shown to be two to three times higher than those recommended by NBR ABNT 13969/1997. The results also pointed out possible incompatibilities between the actual flows and the flows adopted based on the current norms for mining projects, with additional repercussion on the project premises adopted. In qualitative terms, the results indicated the mining site sanitary sewage, in general, presented characteristics of diluted effluents with little organic matter. Finally, the results of the concentration of this effluent presented a percentage of violation to DN COPAM / CERH 01/08 of 13% for the larger CSTP and between 5% and 8% for the smaller and medium CSTPs, in approximately 4.5 years of monitoring.